Determination of pepsin by capillary electrophoresis using mixed polymer coated capillary with switchable properties toward protein adsorption/desorption. Issue 11 (11th April 2022) - Li, Mengqin; Wang, Yuchen; He, Kang; Wang, Yanmei
Abstract : In this work, a simple online preconcentration method for quantitative detection of pepsin was realized by using the binary mixed polymer brushes coated capillary with switchable properties toward protein adsorption. Firstly, the binary mixed polymer brushes were prepared by grafting poly(2‐methyl‐2‐oxazoline) and poly(4‐vinylpyridine) onto the inner wall of the capillary through a polydopamine anchor. Then the coatings were characterized by X‐ray photoelectron spectrometer and electroosmotic flow measurement. The results indicated that the composition of coating could be controlled by varying the feed ratio of poly(2‐methyl‐2‐oxazoline) to poly(4‐vinylpyridine) and the inner surface charge could be tuned toward the change of pH and ionic strength. The results showed that when the poly(2‐methyl‐2‐oxazoline)/poly(4‐vinylpyridine) mass ratio was 80/20, the highest online preconcentration effect was obtained and the sensitivity enhancement factor was 6.3. Moreover, satisfactory sensitivity (limit of detection: 7.5 ng/mL) and good repeatability were obtained with the online preconcentration method. The polymer‐coated capillary was still stable for online preconcentration and detection of pepsin after 50 consecutive runs. Last, the proposed method was used successfully to online preconcentrate pepsin in the saliva matrix.